Notes on Early Land Plants Today. 45. A correction - Váňa, Jíri; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2013)
Váňa et al. (2013) elevated Anastrophyllum subgen. Schizophyllum (Schuster 1969: 739) to generic rank as Schizophyllum (R.M.Schust.) Váňa & L.Söderstr. (2013: 16), overlooking the genus Schizophyllum Nuttall (1841: 452; Asteraceae) and, thereby creating an illegitimate later homonym. This is corrected here by publication of the new genus Schizophyllopsis and the transfer of all species of Schizophyllum (R.M.Schust.) Váňa et al. to that genus. Despite the generic name itself being illegitimate, names published under Schizophyllum (R.M.Schust.) Váňa & L.Söderstr. are legitimate under ICN Art. 55.1 (see below).